Cinematic Rendering in Anatomy: A Crossover Study Comparing a Novel 3D Reconstruction Technique to Conventional Computed Tomography. Issue 1 (7th July 2020) - Binder, Johannes S.; Scholz, Michael; Ellmann, Stephan; Uder, Michael; Grützmann, Robert; Weber, Georg F.; Krautz, Christian
Abstract : Integration of medical imaging into preclinical anatomy courses is already underway in many medical schools. However, interpretation of two‐dimensional grayscale images is difficult and conventional volume rendering techniques provide only images of limited quality. In this regard, a more photorealistic visualization provided by Cinematic Rendering (CR) may be more suitable for anatomical education. A randomized, two‐period crossover study was conducted from July to December 2018, at the University Hospital of Erlangen, Germany to compare CR and conventional computed tomography (CT) imaging for speed and comprehension of anatomy. Sixteen students were randomized into two assessment sequences. During each assessment period, participants had to answer 15 anatomy‐related questions that were divided into three categories: parenchymal, musculoskeletal, and vascular anatomy. After a washout period of 14 days, assessments were crossed over to the respective second reconstruction technique. The mean interperiod differences for the time to answer differed significantly between the CR–CT sequence (−204.21 ± 156.0 seconds) and the CT–CR sequence (243.33 ± 113.83 seconds; P  < 0.001). Overall time reduction by CR was 65.56%. Cinematic Rendering visualization of musculoskeletal and vascular anatomy was higher rated compared to CT visualization ( P  < 0.001 and P  = 0.003), whereas CT visualization of parenchymal anatomy received a higher scoring than CR visualization ( P  < 0.001). No carryover effects were observed. A questionnaire revealed that students consider CR to be beneficial for medical education. These results suggest that CR has a potential to enhance knowledge acquisition and transfer from medical imaging data in medical education.